1993
DOI: 10.1093/jn/123.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Calcium and Vitamin D on Colon Epithelial Cell Proliferation and 1,2-Dimethylhydrazine-Induced Colon Carcinogenesis in Rats Fed High Fat Diets

Abstract: We investigated whether increased levels of dietary calcium and vitamin D could inhibit colon carcinogenesis in rats injected with a single dose of 1,2-dimethylhydrazine. Rats were given a single subcutaneous injection (200 mg/kg body wt) 2 wk before they were fed purified diets containing 20% fat for 32 wk. Diets contained one of three levels of calcium (5, 10 or 15 g/kg diet) as calcium gluconate and one of three levels of vitamin D (0.025, 0.05 or 0.1 mg/kg diet) as cholecalciferol in a 3 x 3 factorial desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Because calcium and vitamin D interact metabolically in the gut to influence absorption [16], the synergy between these two compounds has been studied elsewhere, including cancer research. Both animal and human models show a stronger association between vitamin D supplementation and reduced risk of carcinogenesis in those on a high-calcium diet [7,8,14,17,18]. Despite these promising studies, the joint association of vitamin D and calcium with QoL in cancer patients is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Because calcium and vitamin D interact metabolically in the gut to influence absorption [16], the synergy between these two compounds has been studied elsewhere, including cancer research. Both animal and human models show a stronger association between vitamin D supplementation and reduced risk of carcinogenesis in those on a high-calcium diet [7,8,14,17,18]. Despite these promising studies, the joint association of vitamin D and calcium with QoL in cancer patients is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5 Activation of vitamin D receptors (VDRs) present in many cell types, including colorectal epithelial cells, can inhibit proliferation, angiogenesis and invasiveness, and studies in animal models indicate that vitamin D supplementation can lower the incidence and metastatic potential of intestinal tumors. [6][7][8][9] Ecological studies correlating sunlight exposure with cancer incidence provided the first evidence that vitamin D levels are inversely related to CRC development in humans. 10 Subsequent epidemiological studies have reported lower risks of CRA and CRC in individuals with high intakes and circulating levels of vitamin D. [11][12][13][14] Vitamin D plays a crucial role in calcium metabolism, and there is experimental, 15,16 epidemiologic [17][18][19] and clinical trial 20,21 data indicating that high calcium intake may also lower colorectal neoplasia risk.…”
mentioning
confidence: 99%
“…A first studies with positive effect of vitamin D on CRC risk in rats was proposed more than 25 years ago [77]. Later on, many experimental studies and epidemiological investigations have shown that vitamin D can have an antineoplastic effect, inhibiting cell proliferation and promoting apoptosis [78,79] antineoplastic effect in the colon, reducing the risk of colorectal adenoma recurrence [80].…”
Section: Chemopreventionmentioning
confidence: 99%